2013
DOI: 10.1103/physrevd.88.083527
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherical asymmetry and local non-Gaussianity: A consistency condition

Abstract: In this paper we provide a consistency relation between the amplitude of the hemispherical bipolar asymmetry, A, and the amplitude of the primordial non-Gaussianity in the squeezed limit, f NL , as jAj & 10 À1 f NL . We demonstrate that this consistency condition is at work for any model of inflation in which the curvature perturbations are sourced by a single light field with the Bunch-Davies initial condition, irrespective of the number of inflation fields that contribute to the background inflationary expan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 100 publications
5
74
0
Order By: Relevance
“…In this note we show that there is no inconsistency in [17,18] and the results in [17,18] make sense both mathematically and conceptually. In turn, we also comment on the logic of [1] in relating the observed dipole asymmetry to equilateral configurations.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this note we show that there is no inconsistency in [17,18] and the results in [17,18] make sense both mathematically and conceptually. In turn, we also comment on the logic of [1] in relating the observed dipole asymmetry to equilateral configurations.…”
Section: Introductionmentioning
confidence: 95%
“…This kind of modulation can lead to an asymmetry as studied in [13,14,15,16]. In [17] we have shown that such a modulation is due to a non-linear correlation between the long mode and small CMB modes, i.e. the squeezed limit non-Gaussianity.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations